2017
DOI: 10.1177/1359105316685898
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary support for the role of alcohol cues in food cravings and attentional biases

Abstract: This study examined whether alcohol odors, in isolation or when combined with pictures (food vs. alcohol), would influence food attentional biases and cravings. Participants’ cravings and attentional biases to food and alcohol pictures were assessed after exposure to alcohol or water odors (n = 77; mean age = 30.84, 51.9% female, 83.1% Caucasian). Food attentional biases were increased by alcohol odors, but food cravings were increased only by a combination of alcohol odors and food pictures. These effects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…If such conditions are kept constant across measurement points, it may well be that retest-reliability for the FCQ-S is high. More importantly, however, is that the FCQ-S is sensitive to change during various manipulations: scores increase during food cue exposure (e.g., food pictures) or exposure to real food [52,54,[56][57][58][59][60][61] and decrease after exercise [62], methylphenidate ingestion [63], repetitive transcranial magnetic stimulation [64,65], infraslow neurofeedback training [66], and food intake [11,23,59].…”
Section: Reliabilitymentioning
confidence: 99%
“…If such conditions are kept constant across measurement points, it may well be that retest-reliability for the FCQ-S is high. More importantly, however, is that the FCQ-S is sensitive to change during various manipulations: scores increase during food cue exposure (e.g., food pictures) or exposure to real food [52,54,[56][57][58][59][60][61] and decrease after exercise [62], methylphenidate ingestion [63], repetitive transcranial magnetic stimulation [64,65], infraslow neurofeedback training [66], and food intake [11,23,59].…”
Section: Reliabilitymentioning
confidence: 99%
“…To date, little research has focused on how alcohol intoxication can alter food-related AB. One study found that AB towards food cues was increased by smelling alcohol odours, in the absence of alcohol consumption (Karyadi & Cyders, 2019). However, another study showed that the magnitude of food-related AB did not differ between consumption of a placebo-alcohol, and alcoholic doses of 0.3 g/kg or 0.65 g/kg (Monem & Fillmore, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A smaller study in 23 young adults found that while low- (0.3 g/kg) and high-dose (0.65 g/kg) alcohol primers reduced alcohol-cue related AB relative to placebo, AB towards food-cues were sustained across all doses [ 69 ]. Recent evidence has indicated that alcohol (beer) odour increased attentional bias for food-cues, even in the absence of actual alcohol consumption [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…A smaller study in 23 young adults found that while low-(0.3 g/kg) and high-dose (0.65 g/kg) alcohol primers reduced alcohol-cue related AB relative to placebo, AB towards food-cues were sustained across all doses [69]. Recent evidence has indicated that alcohol (beer) odour increased attentional bias for food-cues, even in the absence of actual alcohol consumption [70]. Food and alcohol 'products' are a source of pleasure and a valued component of social spaces (especially within the night-time economy), as well as emotional and cultural life.…”
Section: Food-related Reward and Attentional-biasmentioning
confidence: 97%